Prevalence of Antimicrobial Resistance Among Gram-Positive Isolates in An Adult Intensive Care Unit at A Tertiary Care Center in Saudi Arabia (Global Journal of Medical Research, 2017)
Abstract not found
Keywords: resistance; multidrug resistance; grampositive bacteria